Comparative evaluation of use of cna, fnbA, fnbB, and hlb for genomic fingerprinting in the epidemiological typing of Staphylococcus aureus. - Smeltzer, M S (1997)
We used a genomic fingerprinting protocol to characterize 59 Staphylococcus aureus strains and a single S. intermedius isolate, all of which were previously typed by 13 different methods (F. C. Tenover et al., J. Clin. Microbiol. 32:407-415, 1994). These 60 strains were divided into three groups of 20 strains each, with each group including internal controls. Two of the three groups (groups SB and SC) included 29 strains from four relatively well-defined outbreaks. The epidemiological relationships of the strains in the third group (group SA) were unclear. Fingerprints were established by Southern blotting with HaeIII-digested genomic DNA and a probe mixture consisting of DNA fragments corresponding to the S. aureus collagen adhesin (cna), fibronectin-binding protein (fnbA and fnbB), and beta-toxin (hlb) genes. An unambiguous fingerprint was obtained for all S. aureus isolates. No hybridization signal was observed with S. intermedius. Twenty-seven of the 29 related strains in the SB and SC groups were correctly identified as belonging to one of the four epidemiologically related groups. Our protocol was less successful with respect to the exclusion of unrelated strains. Specifically, only 6 of 11 unrelated strains in the SB and SC groups had a fingerprint that was distinct by comparison to the fingerprints of the outbreak strains. Nevertheless, our protocol was relatively accurate by comparison to the accuracies of the other methods and was one of only six methods that accurately identified all of the repetitive strains included as internal controls.